2022
DOI: 10.1037/abn0000764
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder, drinking to cope, and harmful alcohol use: A multivariate meta-analysis of the self-medication hypothesis.

Abstract: The association between posttraumatic stress disorder (PTSD) and harmful alcohol use has often been explained through the self-medication hypothesis via coping-related drinking motives. However, the magnitude of the indirect effect of PTSD on harmful alcohol use through coping motives is unclear. This study aggregated this indirect effect using a meta-analytic structural equation modeling approach and explored moderators that influenced the indirect effect. We identified articles from PsycINFO, PubMed/MEDLINE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 54 publications
0
11
0
1
Order By: Relevance
“…Taken together, these studies provide support for the self-medication model, highlighting potential mechanisms such as coping-related drinking, emotion regulation, and negative affect (Luciano et al, 2022;Weiss et al, 2022).…”
Section: Theoretical Models Of Ptsd+audmentioning
confidence: 54%
See 1 more Smart Citation
“…Taken together, these studies provide support for the self-medication model, highlighting potential mechanisms such as coping-related drinking, emotion regulation, and negative affect (Luciano et al, 2022;Weiss et al, 2022).…”
Section: Theoretical Models Of Ptsd+audmentioning
confidence: 54%
“…In microlongitudinal studies, such as studies using experience sampling or daily diary designs, which collect a large amount of data typically over moments, days, or weeks, increases in PTSD symptoms precede alcohol use (Sullivan et al, 2020;Dworkin et al, 2021). Taken together, these studies provide support for the self-medication model, highlighting potential mechanisms such as coping-related drinking, emotion regulation, and negative affect (Luciano et al, 2022;Weiss et al, 2022).…”
Section: Theoretical Models Of Ptsd þ Audmentioning
confidence: 85%
“…Here, we sought to replicate those findings in a larger sample and to compare two mediation models that differed in the hypothesized direction of effect by using information on ages of onset of the disorders to establish temporality. The forward model, consistent with the self-medication hypothesis 15,16,17 , posits that M/ADs mediate the relationship between ACEs and SD diagnoses. In the reverse model, consistent with M/ADs being substance induced 18 , SD mediates the relationship between ACEs and M/ADs.…”
Section: Introductionmentioning
confidence: 76%
“…The self-medication hypothesis 15,16,17 , first posited in 1997, states that psychopathology is accompanied by aversive internal states that motivate individuals to use psychoactive substances to relieve them 57 . Research has shown that ACEs negatively impact emotion regulation skills 58,59 , which help individuals modulate distressing emotions in adaptive ways.…”
Section: Discussionmentioning
confidence: 99%
“…Research exploring the PTSD–alcohol use co-occurrence highlights the bidirectional and transactional associations between PTSD symptomatology and the maintenance and/or exacerbation of alcohol use over time through the use of alcohol use to cope with negative emotional states (Brady et al, 2004; Hawn, Cusack, et al, 2020). For instance, adults with PTSD symptoms may use alcohol to cope (i.e., self-medicate; Khantzian, 1985) with the symptoms of PTSD (Haller & Chassin, 2014; Luciano et al, 2022). Alcohol craving has also been found to increase during periods of time when PTSD symptoms are elevated (Possemato et al, 2015; Simons et al, 2018; Simpson et al, 2014).…”
mentioning
confidence: 99%